Analysis of the modernity of entrepreneurial attitudes in the success of MSMEs, coffee shops fostered by Medan City Cooperatives - Fitriani Fitriani; Mhd Buhari Sibuea; Tri Martial; Faiz Ahmad Sibuea (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
Coffee shop MSMEs have an important role in the economy and are a favorite business in Medan City. The purpose of this study is to analyze the level of modernity of entrepreneurial attitudes of coffee shop MSMEs fostered by the Medan City Cooperative Office, analyze the performance of coffee shop MSME success, and analyze the influence of modernity of entrepreneurial attitudes on the success of coffee shop MSMEs fostered by the Medan City Cooperative Office. This study was conducted in Medan City. The sample of this study was all coffee shop MSMEs fostered by the Medan City Cooperative Office with a total sample of 36 coffee shop MSMEs. The collected data will be analyzed qualitatively with Likert scale measurements and SEM-PLS. The results show that the level of modernity of entrepreneurial attitudes has a total average score of 140.8 with a high category and an average percentage of 78.2%. While the performance of coffee shop MSME success has a total average score of 143.9 with a high category and an average percentage of 79.9%. Furthermore, from the results of the SEM-PLS analysis, it can be seen that there is an influence of the modernity of the entrepreneurial attitudes of coffee shop MSME actors on the success of coffee shop MSMEs.